PENGARUH PENDIDIKAN GIZI DENGAN MEDIA SAMPUL BUKU TERHADAP PENGETAHUAN DAN SIKAP TENTANG ANEMIA REMAJA PUTRI (studi pada siswi kelas VII di SMP Teuku Umar Semarang) - Dini Indah Fauziah; M. Zen Rahfiluddin; Apoina Kartini (Jurnal Kesehatan Masyarakat, 2019)
Adolescent girls are a group that is prone to nutritional problems, one of which is iron deficiency, causing anemia. The influencing factor is the lack of knowledge and attitudes of young women about anemia. Efforts to improve knowledge and attitudes in young women in anemia health problems can be through nutrition education. This study aims to analyze the effect of nutrition education by media education on the cover of books on knowledge and attitudes about anemia in adolescent girls at Teuku Umar Middle School Semarang. The cover of the book contains the understanding of anemia, signs of anemia, anemia prevention and also supported by nutrition education materials about anemia. Data collection used was the Pre-Post Test One Group Design design through filling out questionnaires regarding knowledge and attitudes about adolescent anemia, with a total sample of 36 respondents being counted using purposive sampling. Data analysis using the Wilcoxon Signed Rank Test because the data is not normal. The results showed that the influence of education using a book cover on young women in Teuku Umar Middle School Semarang with a significance value of p-value = 0.001, to the level of knowledge that before intervention 16.7% had increased to 94.6% and increased attitudes in giving good intervention category of 66.7% to 91.7% indicated by a significance value of p-value = 0.001. The conclusion of this study is the influence of nutrition education with book cover media on the level of knowledge and attitudes about Adolescent Girls' Anemia. Schools and students are expected to be able to increase their knowledge and attitudes in the prevention of adolescent anemia.